The Potential and Hurdles of Targeted Alpha Therapy – Clinical Trials and Beyond - Elgqvist, Jorgen; Frost, Sofia; Pouget, Jean-Pierre; Albertsson, Per (Frontiers in Oncology, 2014)
This article presents a general discussion on what has been achieved so far and on the possible future developments of targeted alpha (α)-particle therapy (TAT). Clinical applications and potential benefits of TAT are addressed as well as the drawbacks, such as the limited availability of relevant radionuclides. Alpha-particles have a particular advantage in targeted therapy because of their high potency and specificity. These features are due to their densely ionizing track structure and short path length. The most important consequence, and the major difference compared with the more widely used β–-particle emitters, is that single targeted cancer cells can be killed by self-irradiation with α-particles. Several clinical trials on TAT have been reported, completed, or are on-going: four using 213Bi, two with 211At, two with 225Ac, and one with 212Pb/212Bi. Important and conceptual proof-of-principle of the therapeutic advantages of α-particle therapy has come from clinical studies with 223Ra-dichloride therapy, showing clear benefits in castration-resistant prostate cancer, and has recently been approved by the Food and drug Administration (FDA).